An Optimized Measurement Method for Magnetic Properties of Permalloy Sheet under Demagnetization - Shi, Minxia; Zhang, Xu; Yang, Jianzhi; Yuan, Shuai; Wang, Ling (IEEE transactions on instrumentation and measurement, 2022)
Generally, a permalloy sheet is applied as the major shielding material for weakening the environmental magnetic field interference in a field of high-precision measurement. The demagnetization for a permalloy sheet determines its shielding performance; therefore, an enhanced method for measuring the magnetic properties under degaussing excitation is proposed in this paper. The excitation apparatus and a feedback control system are designed for regulating the B curve of a permalloy sheet as the desired amplitude and waveform. Furthermore, a method for applying degaussing excitation is proposed and the corresponding measurement approach under such magnetic conditions is investigated. Finally, the dynamic Jiles-Atherton model is combined with a finite element method (FEM) algorithm for applying the tested data to the residual magnetic field calculation of a scaled-down model. The agreement between the calculated and tested remanence distribution indicates that the proposed measurement method is reliable and applicable.